(untitled) (CIPEEX, 2025)
Kangaroo Mother Care (KMC) is a simple and low-cost intervention that involves skin-to-skin contact between the newborn and the caregiver, and it has shown important benefits for premature and low-birth-weight infants. The purpose of this work was to explore the effects of KMC on stability, feeding tolerance, and survival in the neonatal intensive care setting. Evidence from randomized controlled trials and meta-analyses shows that KMC helps regulate physiological parameters such as respiratory and heart rate, oxygen saturation and temperature. Particularly, a trial with 168 preterm infants reported that babies receiving KMC had better oxygen levels, more stable vital signs, reached full enteral feeding sooner, and experienced fewer cases of feeding intolerance compared to those under standard care, although no clear differences were found in weight gain or length of stay. Furthermore, a large multicenter study also demonstrated that immediate KMC in infants weighing 1.0–1.799 kg reduced mortality within 28 days compared to conventional care where KMC was delayed until stabilization. Altogether, current evidence supports KMC as a safe and effective practice that improves clinical outcomes and infant survival, reinforcing its early use in neonatal intensive care, especially in hospitals with limited resources.